The Samurai Sword : - Yumoto, John M. (Charles E. Tuttle Company, 1971)
The samurai sword: a symbol of the spirit of old Japan, it embodies the samurai's steel discipline, unswerving devotion and peerless skill. With its creation, a feat of craftsmanship passed down by generations of artisans, the samurai sword is generally considered to be superior even to the famed blades of Western Damascus and Toledo. The Samurai Sword Handbook is a precise exploration of the samurai sword designed for sword collectors as well as anyone intrigued by these ancient blades. Detailing the origins and development of the samurai sword, its historical background, styles, famous schools and differences in construction, this revised edition of the classic reference outlines methods of identifying and researching the sword, as well as caring for it properly. This must-have for sword lovers is sure to be a bestseller.